Reproductive phenology of useful Seasonally Dry Tropical Forest trees: Guiding patterns for seed collection and plant propagation in nurseries - Luna-Nieves, Adriana L.; Meave, Jorge A.; Morellato, Leonor Patrícia Cerdeira [UNESP]; Ibarra-Manríquez, Guillermo (Elsevier, 2017)
The propagation in nurseries of native plant species potentially useful for agroforestry, silvopastoral and restoration programs is hindered by an inadequate supply of high quality seed. Limitations in our knowledge on the phenological patterns of native species result in the lack of efficient collecting protocols. Here we analyze the reproductive phenology of 14 native tree species from Seasonally Dry Tropical Forest (SDTF) that are widely used in reforestation and restoration programs. We conducted monthly observations during five years through a community-based monitoring program in two conservation areas within the Zicuirán-Infiernillo Biosphere Reserve (West Mexico) to assess the flowering and fruiting phenology of 149 marked trees (7–20 trees per species). For each species we described the phenophase intensity, duration, seasonality, synchrony and frequency. We related the intensity of reproductive phenology to climatic variables (photoperiod, precipitation and temperature). We identified three main phenological strategies of SDTF species that differ in timing and climatic triggers: (1) flowering and fruiting exclusively in the rainy season; (2) flowering in the rainy season and fruiting in the dry season; and (3) flowering and fruiting exclusively in the dry season. For each phenological strategy we make recommendations of optimal collecting seeds schedules. The community-based monitoring program, which involves the participation of local social actors, guaranteed the success of long-term phenological monitoring. Our study provides valuable information on both the inter-annual and inter-specific variation of the phenological patterns of tree species of forestry interest, and demonstrates that qualitative descriptions of population-level phenological attributes is an essential input to develop adaptive management programs.
Keywords: Adaptive management; Community-based monitoring program; Environmental trigger; Flowering time; Fruiting time; Seed collection